On Integration of One Class of Systems of Lax-Type Equations - Lunyov, A.A.; Oliynyk, E.V. (Журнал математической физики, анализа, геометрии, 2015)
A nonlinear system of Lax-type equations is studied. The system is the basis of the construction of triangular models for commutative systems of linear non-selfadjoint bounded operators. Some of its solutions for n = 4 are described. In one of the cases, the general solution is explicitly expressed in terms of special (elliptic) functions. Исследуется нелинейная система уравнений типа Лакса, которая лежит в основе построения треугольных моделей для коммутативных систем линейных несамосопряженных ограниченных операторов. Описаны некоторые ее решения при n = 4. В одном из случаев общее решение явно выражается в терминах специальных (эллиптических) функций. Досліджується нелінійна система рівнянь типу Лакса, яка лежить в основі побудови трикутних моделей для комутативних систем лінійних несамоспряжених обмежених операторів. Описано деякі її розв'язки при n = 4. В одному з випадків загальний розв'язок явно виражається в термінах спеціальних (еліптичних) функцій.